Balance expertise is associated with superior spatial perspective-taking skills - Kirsten Hötting and Ann Kathrin Rogge and Laura A. Kuhne and Brigitte Röder (Brain Sciences, 2021)
Balance training interventions over several months have been shown to improve spatial cognitive functions and to induce structural plasticity in brain regions associated with visual-vestibular self-motion processing. In the present cross-sectional study, we tested whether long-term balance practice is associated with better spatial cognition. To this end, spatial perspective-taking abilities were compared between balance experts (n = 40) practicing sports such as gymnastics, acrobatics or slacklining for at least four hours a week for the last two years, endurance athletes (n = 38) and sedentary healthy individuals (n = 58). The balance group showed better performance in a dynamic balance task compared to both the endurance group and the sedentary group. Furthermore, the balance group outperformed the sedentary group in a spatial perspective-taking task. A regression analysis across all participants revealed a positive association between individual balance performance and spatial perspective-taking abilities. Groups did not differ in executive functions, and individual balance performance did not correlate with executive functions, suggesting a specific association between balance skills and spatial cognition. The results are in line with theories of embodied cognition, assuming that sensorimotor experience shapes cognitive functions.
Keywords: Balance; Motor expertise; Physical activity; Spatial cognition